1981
DOI: 10.1038/hdy.1981.5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of the frequency trajectories in the process of fixation of null genes at duplicated loci

Abstract: A new numerical method, based on the stochastic differential equations, has been applied to the problem of the fixation of null alleles at duplicated loci. The results reported here were obtained under the assumption that individuals carrying homozygous null genes at both of the duplicated loci are lethal, but all the other genotypes are normal. The mean and median time for null alleles to fix can vary from 2N to lOON or more, depending on the mutation rate and the population size, where N is the population si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Therefore T r is approximately equal to [log(1/l)]N for a large population, which indicates that T r for unlinked loci is asymptotically linear to N. Maruyama and Takahata (1981) observed that under the DNR model T r for unlinked duplication is much larger than that of linked in a large population. Lynch and Force (2000) examined the predictions of Eq.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore T r is approximately equal to [log(1/l)]N for a large population, which indicates that T r for unlinked loci is asymptotically linear to N. Maruyama and Takahata (1981) observed that under the DNR model T r for unlinked duplication is much larger than that of linked in a large population. Lynch and Force (2000) examined the predictions of Eq.…”
Section: Introductionmentioning
confidence: 94%
“…As might be expected from both the prevalence of polyploidy and its perceived significance, the subject of gene duplication has long attracted the interest of population geneticists [28,106,129,142,146,148,216,217,220]. This work, which traces back at least as far as Haldane and Fisher in the 1930s [53,73], models one or more aspects of gene diversification or silencing using as input parameters factors such as mutation rates, fitness differences among alleles at duplicated loci, and effective population sizes.…”
Section: Evolution Of Duplicated Genesmentioning
confidence: 99%
“…If gene frequencies are not equal at the two loci, as might be expected with drift or unequal mutation rates, then the inbreeding depression will more closely resemble that with single locus inheritance. Fixation of one of the deleterious alleles can occur when there are unequal mutation rates at the two loci (Christiansen & Frydenberg, 1977) or when the population size is small (Haldane, 1933;Nei, 1969;Ohno, 1972;Nei & Roychoudhury, 1973;Maruyama & Takahata, 1981). Gene silencing by the fixation of null alleles at duplicate loci has occurred frequently in the evolution of presumed ancient polyploids like salmonid and catostomid fishes (Allendorf, 1976;Ferris & Whitt, 1977;Li, 1980) and ferns (Werth eta!., 1985;Bryan & Soltis, 1987;Gastony, 1991;Werth & Windham, 1991).…”
Section: Idmentioning
confidence: 99%